PT Siantar Top Tbk's Strategy in Facing Competition in the Processed Food Industry - Francisca Harroviantin; Werner R. Murhadi (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study is to analyze what strategic choices the company can make in order to survive with the future situation. The key concept in this research is strategy formulation, where the quantitative method used includes industrial management steps applied by PT Siantar Top Tbk in facing processed food business competition. The results of research on the internal and external environment get the strengths, weaknesses, opportunities, and challenges (SWOT) of PT Siantar Top Tbk. The SWOT analysis is then entered into several matrices, including EFE and IFE, CPM, TOWS, SPACE, BCG, IE, GSM, and QSPM. The final recommendation obtained is that the strategic choice of PT Siantar Top Tbk is to diversify product segments, and focus on expanding overseas markets by utilizing digital technology, optimizing e-commerce platforms to expand product range and reach a wider audience efficiently.